2015
DOI: 10.1371/journal.pone.0131712
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Analysis for Program Implementation

Abstract: This paper introduces the use of social network analysis theory and tools for implementation research. The social network perspective is useful for understanding, monitoring, influencing, or evaluating the implementation process when programs, policies, practices, or principles are designed and scaled up or adapted to different settings. We briefly describe common barriers to implementation success and relate them to the social networks of implementation stakeholders. We introduce a few simple measures commonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
281
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 253 publications
(294 citation statements)
references
References 72 publications
2
281
0
11
Order By: Relevance
“…Additional analyses should be conducted to determine if there are significant differences by context with other constructs (e.g., knowledge/familiarity; perceptions of validity; predicted effects) and also to examine whether contextual variables interact in complex ways with these constructs. Attention should be paid to additional elements of context that include educators' perceptions of school supportiveness (e.g., professional development, collegiality; Johnson, 2015), as well as other factors, including perceptions of leadership support for policy (Valente et al, 2015) on the use of value-added for educator evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Additional analyses should be conducted to determine if there are significant differences by context with other constructs (e.g., knowledge/familiarity; perceptions of validity; predicted effects) and also to examine whether contextual variables interact in complex ways with these constructs. Attention should be paid to additional elements of context that include educators' perceptions of school supportiveness (e.g., professional development, collegiality; Johnson, 2015), as well as other factors, including perceptions of leadership support for policy (Valente et al, 2015) on the use of value-added for educator evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…System dynamics is just one example of the larger class of systems science methods that may be useful in translational research, practice, and policy efforts [29,62,72,73]. Another approach, organizational network analysis, has already proven highly relevant to T4 translation and can improve our understanding of the adoption and implementation of evidence-based interventions [74]. Similar to system dynamics, agent-based modeling can be used to test combinations of efficacious intervention strategies in silico, improving our understanding of potential effectiveness prior to costly real-world implementation [75][76][77].…”
Section: Original Researchmentioning
confidence: 99%
“…The connections within most regions where GB has been implemented are not broad or extensive yet, but it is clear that communication is occurring. While such communication may seem trivial, when creating a new network, it is essential to demonstrate such communication to justify continued effort at building and sustaining the network, and it is valuable to assess success in programme implementation (Valente, 2012;Valente, Palinkas, Czaja, Chu, & Brown, 2015). The tobacco dependence treatment collaboration network data also indicated that professional and organisations ties are forming through GB activities and efforts, and that the GB network is influencing contact and introducing resources concerning tobacco dependence treatment to its members.…”
Section: Resultsmentioning
confidence: 99%